Variations in the End-Use Quality of Whole Grain Flour Are Closely Related to the Metabolites in the Grains of Pigmented Wheat (Triticum aestivum L.) - Bin Wang; Jie Kang; Shuaiqi Wang; Fasih Ullah Haider; Yingxin Zhong; Peng Zhang (Plants)
Whole grain flour is considered a part of a healthy diet, especially when produced with pigmented wheat (Triticum aestivum). However, the specific metabolic pathways and mechanisms by which these metabolites affect the end-use quality of pigmented wheat varieties still need to be better understood. This study examined the relationship between metabolite concentrations and the end-use quality of three wheat varieties: common wheat (CW, JM20), black wheat (BW, HJ1), and green wheat (GW, HZ148). The study’s findings revealed significant differences in the accumulation of metabolic substances among the various pigmented wheat varieties. Specifically, BW and GW exhibited notably higher levels of amino acids, derivatives, and lipids than CW. The study’s findings revealed significant differences in the accumulation of metabolic substances among the various pigmented wheat varieties. Specifically, BW and GW exhibited notably higher levels of amino acids and their derivatives and lipids than CW. Amino acid derivatives, such as glutathione and creatine, are compounds formed through chemical modifications of amino acids and play crucial roles in antioxidative defense and energy metabolism. The gliadin and glutenin content of BW increased by 12% and 2%, respectively, compared to CW, due to elevated levels of amino acids and their derivatives, whereas GW was notable for its higher globulin content (an increase of 11.6%). BW was also distinguished by its exceptionally high anthocyanin content, including cyanidin-3-O-(6-O-malonyl-beta-D-glucoside) (23.2 μg g−1), cyanidin-3-O-glucoside (6.5 μg g−1), and peonidin-3-O-glucoside (2.3 μg g−1), which surpassed the levels found in both CW and GW (which approached zero). However, BW had lower gluten content, resulting in a greater weakening and reduced development and stability times. Conversely, GW exhibited an increased lipid metabolism, which was associated with a higher starch and gluten content, improving the maximum tensile resistance. Overall, the pigmented wheat varieties offer superior nutritional profiles and processing advantages, necessitating further research to optimize their commercial use.